Positive Reinforcement Techniques as a Media to Improve Social Interaction Capabilities in Adolescent with Hebefrenic Schizophrenia - Karina Kandhi Krisnawardhani; IGAA Noviekayati (Proceedings of The ICECRS, 2020)
This study aims to intervene in one of the adolescent patients with hebephrenic schizophrenia who are in RSJ Menur Surabaya. The Researcher gave an intervention in the form of behavioral therapy which is a positive reinforcement to be able to improve the ability of social interaction with others, dare to socialize with the environment or actively participate in groups. The intervention carried out eight meeting sessions. Each session has a different target according to indicators of social interaction. If the client is able to reach the target, the researcher gives an reward in the form of praise, food or activities (for example: drawing) that he likes.This therapy is believed to be able to increase the ability of social interaction. The method used in study is an experimental with a case study approach. Before the behavioral interventions that appear on the client are ideology of greatness, visual and auditory hallucinations, don’t want to communicate with others, like to be alone, lack confidence, and do not participate in group activities. After being given an intervention the client realizes his mind is only an imagination, no longer hears whispers, wants to communicate with others, and is active in a group. The results of this study indicate that positive reinforcement is effectively used as a medium to improve the ability af social interaction on the subject.